2021
DOI: 10.3390/antiox10010062
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Korean Black Ginseng Extract through ER Stress Pathway

Abstract: The excessive release of reactive oxygen species (ROS) can result in the development of chronic inflammation. The mechanisms involved in inflammation are various, with endoplasmic reticulum (ER) stress known to be among them. We have previously shown that black ginseng (BG) reduced lipid accumulation in and enhanced the antioxidant function of the liver in vitro and in vivo mostly due to ginsenoside Rb1, Rg3 and Rk1 components. Therefore, this study investigated the antioxidant effect of BG on the intestines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…A type of ginseng called black ginseng also showed a role in immunity by reducing ROS and NO followed by inflammation. It has also been shown to have antioxidant effects through ER mechanism [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A type of ginseng called black ginseng also showed a role in immunity by reducing ROS and NO followed by inflammation. It has also been shown to have antioxidant effects through ER mechanism [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that decreasing ER stress levels was related to the inhibition of ROS production. An et al indicated that black ginseng reduced ROS production in NAFLD through an ER stress-related pathway [32]. And another research observed that rosmarinic acid alleviated acrylamide-induced hepatic oxidative stress and decreased ER stress, which also implied that ER stress was a potential modulator of ROS production [33].…”
Section: Irisin Decreases Er Stressmentioning
confidence: 99%
“…It contains a diverse range of bioactive compounds, including well-known ginsenosides, acidic polysaccharides, and the recently identified gintonin [1]. Ginseng possesses a wide range of therapeutic properties, including anti-aging, anti-fatigue, antioxidant, vasodilatory, anti-inflammatory, antidiabetic, and antipsychotic effects [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%